Leitura, Argumentação E Referenciação: Uma Possibilidade De Exploração Textual Para A Educação Básica (PERcursos Linguísticos, 2023)
In this article, we discuss the importance of referencing in the reading process, mainly considering the contributions of Text Linguistics and the implications for the teacher's work in the classroom. To do so, initially, we made theoretical considerations about reading (KOCH, 2002, 2015; KOCH and ELIAS, 2012, 2016; SOLÉ, 1998), argumentation (KOCH and ELIAS, 2014a, 2014b, 2016; CAVALCANTE et al, 2014) and referencing (especially from KOCH, 2002; 2015). Next, we carried out an analysis of an opinion article that addresses a controversial issue which gained great repercussion in the media, with emphasis on the use of referencing in the text and the impact of using these elements for reading. Finally, we present a possibility of exploring the aforementioned text, with the aim that, based on adaptations and expansions carried out by the teachers, it will contribute to the qualification of the reading competence of argumentative texts by Basic Education students.